Basic didactic principles and mathematical competencies in teaching mathematics (Journal of Pedagogical Inventions and Practices, 2023)
The article outlines the main didactic principles and mathematical competencies in teaching mathematics. In the process of teaching mathematics, the student will begin to overcome various difficulties, the richer his mental activity, the more often an atmosphere of creative upsurge is created in the lesson, the more effective teaching and education. The reader will find many specific examples of the implementation of this thesis in teaching mathematics.